2020
DOI: 10.1177/0885066620933798
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of Opioid Therapy at Transitions of Care in Critically Ill Patients

Abstract: Purpose: Opioids are one of the high-risk medication classes that are administered to critically ill patients during their intensive care unit (ICU) stay. However, little attention has been given to inpatient opioid prescribing practices, especially in critically ill patients. The purpose of our study was to characterize opioid prescribing practices across 2 transitions of care during an inpatient hospital stay: medical ICU (MICU)/intermediate care unit (IMC) to floor and floor to hospital discharge and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
(26 reference statements)
1
14
1
Order By: Relevance
“…Similarly, in another retrospective cohort study, cumulative opioid dose was noted to be a potentially important differentiating factor between those who received an opioid at discharge compared with those that did not. 13 Contrary to these findings, our cohort of opioid-naïve patients admitted to the ICU did not demonstrate similar relationships. This could be explained by our increased ability to control for potentially confounding variables, which was a component lacking from previous analyses.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Similarly, in another retrospective cohort study, cumulative opioid dose was noted to be a potentially important differentiating factor between those who received an opioid at discharge compared with those that did not. 13 Contrary to these findings, our cohort of opioid-naïve patients admitted to the ICU did not demonstrate similar relationships. This could be explained by our increased ability to control for potentially confounding variables, which was a component lacking from previous analyses.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition to cumulative hospital opioid exposure, hospital LOS may be a predictor of discharge opioid receipt, consistent with our findings that patients with a discharge opioid prescription had a longer hospital LOS. 13 We evaluated ICU MME exposure, rather than total hospital exposure, based on the primary intent of our study. Non-ICU LOS, rather than total LOS, was utilized because there was an observed difference in the compared groups between total hospital LOS but not ICU LOS.…”
Section: Discussionmentioning
confidence: 99%
“…The model has a good clinical application effect [ 4 ]. Studies have found that the Omaha system has a good effect in patients with hypertension, lung diseases, and urostomy, but it is less used in patients undergoing radical prostatectomy [ 5 ]. Continuing care refers to the ability of patients to continue to receive professional medical care after leaving the original medical environment to promote health recovery [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies evaluating persistent opioid use after critical illness reported ICU opioid doses (23)(24)(25); among opioid-naïve patients, Krancevich et al (23) and Witcraft et al (24) found no association between ICU opioid dose and persistent opioid use), and Tollinche et al (25) observed that patients who received opioids in the ICU were less likely to receive an opioid prescription at discharge. Witcraft et al (24) found that intubation and hospital (but not ICU) opioid dose were associated with continuing opioids at discharge. In our multivariable analyses, neither of these factors was associated with persistent opioid use for OPTA or non-OPTA patients.…”
Section: Discussionmentioning
confidence: 99%